Marvin is a good student and is especially gifted in math. He loves to solve math problems that require him to think outside of the box. So, his teacher presents him with the following riddle:
26 parameters (a to z) are given with the following values:
a = 1, b = 2, c = 3, d = 4, …, z = 26
Calculate the result of the following expressions:
(a – x) * (b – x) * (c – x) * (d – x) * … * (z – x) = ?
Help Marvin to solve this puzzler and find out how to get the answers as quickly as possible.
The solution for this task becomes clear when the multiplication is started backwards.
…. (w-x) * (x-x) * (y-x) * (z-x) = ?
As can be seen, the third to last expression is "(x-x)" which results in "0."
If one of the factors in the multiplication is "0," the result of the total multiplication is "0." Therefore, the solution of this task is "0," too.
If Martin recognizes this, he does not have to go through the complete calculation path to get to the solution.